2020
DOI: 10.3389/fmicb.2020.559165
|View full text |Cite
|
Sign up to set email alerts
|

Translation-Associated Mutational U-Pressure in the First ORF of SARS-CoV-2 and Other Coronaviruses

Abstract: Within 4 months of the ongoing COVID-19 pandemic caused by SARS-CoV-2, more than 250 nucleotide mutations have been detected in ORF1ab of the virus isolated from infected persons from different parts of the globe. These observations open up an obvious question about the rate and direction of mutational pressure for further vaccine and therapeutics designing. In this study, we did a comparative analysis of ORF1a and ORF1b by using the first isolate (Wuhan strain) as the parent sequence. We observed that most of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Hypermutation rather than positive selection may explain many remaining highly recurrent sites. Previous analyses have indicated that the number of C>U mutations is exceptionally high relative to other mutation types in the viral genome [11,26,45,49]. This class of mutations should show increased evidence of recurring multiple times because they experience elevated mutation rates [26].…”
Section: Recurrent Mutations Not Associated With a Lab Reflect The Mumentioning
confidence: 99%
See 1 more Smart Citation
“…Hypermutation rather than positive selection may explain many remaining highly recurrent sites. Previous analyses have indicated that the number of C>U mutations is exceptionally high relative to other mutation types in the viral genome [11,26,45,49]. This class of mutations should show increased evidence of recurring multiple times because they experience elevated mutation rates [26].…”
Section: Recurrent Mutations Not Associated With a Lab Reflect The Mumentioning
confidence: 99%
“…Extremely rapid whole-genome sequencing has enabled nearly real-time tracing of the evolution of the SARS-CoV-2 pandemic [1][2][3][4][5][6]. By leveraging sequence data produced by labs throughout the world, researchers can trace the transmission of the virus across human populations [7][8][9][10][11][12][13][14][15]. Typically, viral evolution is encapsulated by a phylogenetic tree relating all of the virus samples in a large set to one another [6,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this variant has 3 mutations on the Membrane site. The ORF1b and Nucleocapsid region also have 11 and 4 mutation sites respectively [19]. The Spike protein play a critical role in identifying and binding the host cell surface receptors, and mediating the fusion of viral envelope to the cell membrane.…”
Section: Mutation Sites On Omicron Strainmentioning
confidence: 99%
“…These transitions, mostly occurring during the RNA plus strand replication and translation, cannot be corrected by the proof-reading machinery of coronaviruses. Thus, this leads to amino-acid (a.a) substitutions that can be quite drastic for the fitness of a virus or may help the virus to escape the immune response (Di Giorgio et al, 2020;Khrustalev et al, 2020;Ratcliff and Simmonds, 2021). Third, coronaviruses have the capacity to undergo both inter-molecular recombination between 2 distinct molecules and intra-molecular recombination within the same molecule.…”
Section: Diversity Of Coronavirusesmentioning
confidence: 99%